Answer:
10.630
Step-by-step explanation:


(5 - ( - 3)^2 = 64
(5 - ( -2)^2 = 49
49 + 64
113

10.630
I hope this helps
Answer:
OPtion B)
Step-by-step explanation:
2^x is the function of the exponential growth.
Hence , 2^1, 2^2/hour = 4, 2^3 = 6/hr... 2^n=2^n at an amassing rate.
Bacteria is one great example to present the exponential growth. <span>Bacteria are single celled microorganisms. They have a simple cell structure than other organisms because they have no nucleus and no cell membrane. Their control center containing the genetic information si contained in a single loop of DNA. </span>
Answer:
ad
Step-by-step explanation:
s